Ontogenia do óvulo e da semente de espécies de Cuspidaria e Tynanthus (Bignonieae: Bignoniaceae) - Lozasso, Jessyca Alyne (2016)
Recent studies of molecular phylogeny changed significantly the circunscription of various genera of Bignonieae-Bignoniaceae. In a later taxonomic treatment, one of its biggest genera, Arrabidaeae, considered polyphyletic, was the circunscription changed and had its species distributed in the genera Cuspidaria, Fridericia, Tanaecium and Xylophragma. Given the great conservatism of the embryological features of angiosperms, this study aimed to analyze the ovule and seed ontogeny of C. sceptrum (= Arrabidaea sceptrum), C. convoluta and Tynanthus micranthus in search of characters that support the molecular data that allowed the inclusion of Arrabidaea species in Cuspidaria, as well as that can distinguish the Cuspidaria species from his sister's group, Tynanthus. In addition to establish comparisons with Fridericia platyphylla (= Arrabidaea brachypoda), adopted as an external group. The anatropous, unitegmic tenuinucellate ovules, with an endothelium and a hypostase, and with a regular meiosis forming a linear tetrad and developing a Polygonum megagametophyte, are in accordance to the observed in earlier studies of Bignoniaceae species. The ovule primordia rising in zones II and III of the placentae differ from the previously described for other Bignoniaceae. The studied species share the origin of the integument only in the dermal layer with the tribe Jacarandeae, differing from the species of Tabebuia alliance. Cuspidaria and Fridericia species have only a series of ovules per placentae, while T. micranthus has two series of ovules per placentae, proving to be a useful feature to distinguish Cuspidaria from Tynanthus. The absence of fleshy crests placentae and the presence of an integument extension at the micropylar pole of the ovule are shared by Cuspidaria species and F. platyphylla, indicating that they can be more widely distributed in the clade Arrabidaea and allies, although they are absent in T. micranthus. The chalazal haustorium of the endosperm of the three studied species has four cells and it is shared with species of the most basal tribes of the family, Jacarandeae and Tecomeae, but differs from the finds for the Tabebuia alliance and Paleotropical clades, being an important character to distinguish tribes or higher clades. The presence of a membranous envelope composed by an endosperm with a late differentiation and by the endothelium seems to be a synapomorphy for Bignoniaceae and its ontogeny corresponds to the described in recent works. Although the late differentiated endosperm is present in the mature seed, it is scarce, not being the main source of nutrients 4 during germination, so that the seed is characterized as exalbuminous. The integument extension at the micropylar pole of the ovule did not follow the seed expansion, indicating that its function should be restricted to the floral anthesis and could favor the ovule penetration by the pollen tube. The analysis of the morphology of the hilum showed that Cuspidaria species have oval hilum, while Tynanthus species have linear hilum, with some exceptions, indicating the need for additional studies of this feature. Thus, although the results of this study are useful to distinguish Tynanthus and Cuspidaria species, they can not be used to support the new circunscription of Cuspidaria sceptrum (= Arrabidaea sceptrum).